Toward cost‐effective replica placements in cloud storage systems with QoS‐awareness. (23rd September 2016) - Zeng, Lingfang; Xu, Shijie; Wang, Yang; Kent, Kenneth B.; Bremner, David; Xu, Chengzhong
Summary: In this paper, we propose a simulation model to study real‐world replication workflows for cloud storage systems. With this model, we present three new methods to maximize the storage space usage during replica creation, and two novel QoS aware greedy algorithms for replica placement optimization. By using a simulation method, our algorithms are evaluated, through a comparison with the existing placement algorithms, to show that (i) a more evenly distributed replicas for a data set can be achieved by using round‐robin methods in replica creation phase and (ii) the two proposed greedy algorithms, named GS_QoS and GS_QoS_C1, not only have more economical results than those from Chen et al ., but also guarantee the QoS for clients. Copyright © 2016 John Wiley & Sons, Ltd.